Assessment of Acute Kidney Injury in Patients Undergoing Elective Coronary Angiography and Percutaneous Coronary Intervention (Cardiovascular Journal, 2012)
Background: CIN has gained increased attention in the clinical setting, particularly during cardiac intervention but also in many other radiological procedures in which iodinated contrast media are used. There is at present good clinical evidence from well-controlled randomized studies that CIN is a common cause of acute renal dysfunction.Methodology: This was a prospective study conducted among the patients who underwent coronary angiography and percutaneous coronary intervention in the Department of Cardiology, Dhaka Medical College Hospital during January 2010 to December 2010. A total of 111 patients age range from 25 to 75 years were included in the study. Serum creatinine level at baseline and at the end of 48 hours was done in all these patients. Study population was divided into two groups according to development of acute kidney injury (AKI). Group-I = AKI, Group II = Not developed AKI. Results: AKI developed 11.7% of the study patient. DM and Preexisting renal insufficiency were significantly higher in group I patients. HTN was (61.5% Vs 44.9%) higher in group I but not significantly. History of ACE inhibitor/ARB, NSAID intake and LVEF 150 ml), eGFR (